STRATEGI GURU PAI DALAM MENANAMKAN NILAI TOLERANSI ANTARUMAT BERAGAMA DI SEKOLAH NEGERI BERBASIS MASYARAKAT PLURAL - Rayadi; Baili; Mabruri; yulia friska, Sonia; Sriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2021)
This study aims to identify and analyze the strategies employed by Islamic Religious Education (PAI) teachers in instilling inter-religious tolerance values in public schools located within pluralistic communities. Using a qualitative approach with a multi-site case study design, the research involved three PAI teachers, six students from diverse religious backgrounds, two school principals, and one supervisor from two public junior high schools in multicultural regions. Data were collected through semi-structured interviews, participatory observation, and documentation. Data analysis followed the interactive model of Miles and Huberman. The findings indicate that PAI teachers implement four primary strategies: integration of tolerance values into lesson planning and delivery, inclusive behavioral role modeling, facilitation of structured interfaith dialogue, and contextualization of local wisdom. These strategies significantly contribute to fostering mutual respect, reducing religious prejudice, and strengthening social cohesion within the school environment. The study concludes that the role of PAI teachers in pluralistic schools extends beyond doctrinal knowledge transfer to functioning as agents of moderation and social cohesion. Practical implications highlight the need to strengthen teachers’ multicultural competencies, integrate tolerance values into the hidden curriculum, and ensure inclusive school policy support.